Mental state understanding in children with agenesis of the corpus callosum - Lábadi, Beatrix; Beke, Anna M. (Frontiers in Psychology, 2017)
Impaired social functioning is a well-known outcome of individuals with agenesis of the corpus cal-losum. Social deficits in nonliteral language comprehension, humour, social reasoning, and recognition of facial expression have all been documented in adults with agenesis of the corpus callosum. In the present study, we examined the emotional and mentalizing deficits that contributing to the social-cognitive development in children with isolated corpus callosum agenesia, including emotion recog-nition, theory of mind, executive function, working memory, and behavioural impairments as assessed by the parents. The study involved children between the age of six and eight years along with typically developing children who were matched by IQ, age, gender, education, and caregiver’s education. The findings indicated that children with agenesis of the corpus callosum exhibited mild impairments in all social factors (recognizing emotions, understanding theory of mind), and showed more behavioural problems than control children. Taken together, these findings suggest that reduced callosal connectivity may contribute to the development of higher-order social-cognitive deficits, involving limits of complex and rapidly occurring social information to be processed. The studies of AgCC shed lights of the role of structural connectivity across the hemispheres in neurodevelopmental disorders.